Investigation on cognitive status and influencing factors of urology nurses in preventing catheter-associated urinary tract infection (泌尿外科护士预防导尿管相关尿路感染的认知现状及影响因素分析) - PAN Liulin (潘柳霖); QUAN Xiangfeng (全翔凤) (中西医结合护理)
Objective To investigate the cognitive status and influencing factors of urology nurses in preventing catheter-associated urinary tract infections(CAUTI). Methods From March to May 2022, 120 urology clinical nurses were selected as the research objects by convenience sampling method, and general information questionnaires and the CAUTI prevention cognition scale were distributed for questionnaire survey to investigate nurses' cognitive level of CAUTI. Results Totally 110 (91. 67%)valid questionnaires were collected. The knowledge score of urology nurses on preventing CAUTI was 87. 22 +-a> 8. 00, indicating a relatively low level of cognition . Multiple linear regression analysis showed that different age, length of service, professional title, and hospital level were the influencing factors of urology nurses' cognition of preventing CAUTI (P£¼0. 05). Conclusion The cognition of urology nurses on the prevention of CAUTI needs to be improved, and the training of urology nurses in low seniority, low professional title and secondary hospitals should be strengthened. (目的 调查泌尿外科护士预防导尿管相关尿路感染的认知现状, 分析影响因素。方法 2022年3月—5月采用便利抽样法选取广西壮族自治区医疗机构120名泌尿外科临床护士为研究对象, 发放一般资料调查表和预防导尿管相关尿路感染认知量表进行问卷调查, 调查护士导尿管相关尿路感染的认知水平。结果 回收有效问卷110(91. 67%)份。泌尿外科护士预防导尿管相关尿路感染的知识得分为(87. 22±8. 00)分, 处于较低水平。多元线性回归分析显示, 不同年龄、工龄、职称、医院级别是泌尿外科护士预防导尿管相关尿路感染认知的影响因素(P＜0. 05)。结论 泌尿外科护士对预防导尿管相关尿路感染的认知有待提高, 应加强对低年资、低职称和二级医院的泌尿外科护士培训。)